Methodology of Deciding Fatwa in Islam: A Case Study of Legal Decision Making in NU Organization - Abd Moqsith (Islamic Studies Journal for Social Transformation, 2017)
There are problems of islamic jurisprudence existing in society, but Qur'an and hadith as the references of shari'a are keep stagnant. Text of Qur'an and hadith are stagnant-without development, while the problems of jurisprudence are still growing. In fact, it is impossible to leave the problems without a solution. In that context, like other Islamic organizations, Nahdhatul Ulama (NU) actively issues religious fatwas. In order to keep the religious fatwa still based on the islamic law, NU has established a procedure of bahtsul masail, which is a scientific forum to respond the problems of jurisprudence, both individual and public jurisprudence related to public affairs. In delivering fatwa or answering the problems of jurisprudence, NU likely only picks up old Jurisprudence reference which are relevant to the problems. However, NU is allowed to perform ilhaqul masa'il binadhairiha, even istinbath in jama'i if the problems of Jurisprudence which can not be solved with the old Jurisprudence reference.